Electro-Conductive Modification of Polyvinylidene Fluoride Membrane for Electrified Wastewater Treatment: Optimization and Antifouling Performance - Jinzhuo Shi; Yisong Hu; Songhua Li; Wenqian Xiao; Yuan Yang; Jiayuan Ji (Membranes)
Electro-conductive membranes coupled with a low-voltage electric field can enhance pollutant removal and mitigate membrane fouling, demonstrating significant potential for electrified wastewater treatment. However, efficient fabrication of conductive membranes poses challenges. An in situ oxidative polymerization approach was applied to prepare PVDF-based conductive membranes (PVDF-CMs) and response surface methodology (RSM) was adopted to optimize modification conditions enhancing membrane performance. The anti-fouling property of the conductive membranes was analyzed using model pollutants. The results indicate that when the concentrations of the pyrrole, BVIMBF4, and FeCl3·6H2O are 0.9 mol/L, 4.8 mmol, and 0.8 mol/L, respectively, the electrical resistance of the PVDF-CM is 93 Ω/sq with the water contact angle of 31°, demonstrating good conductivity and hydrophilicity. Batch membrane filtration experiments coupled with negative voltage indicated that when an external voltage of 2.0 V is applied, membrane fouling rates for the conductive membrane filtering BSA and SA solutions are reduced by 17.7% and 17.2%, respectively, compared to the control (0 V). When an external voltage of 0.5 V is applied, the membrane fouling rate for the conductive membrane filtering HA solution is reduced by 72.6%. This study provides a valuable reference for the efficient preparation of conductive membranes for cost-effective wastewater treatment.